Environmentally Conscious Tourism: Lessons from the Successful Rehabilitation of Boracay Island - Sabandal, Chriszela; Gumban, Gynnyn (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to explore the lessons learned from the successful rehabilitation of Boracay Island. The Boracay rehabilitation is a significant government intervention designed to address the environmental challenges posed by tourism. The study focuses on understanding the community's perspective on environmentally-conscious tourism, evaluating the effectiveness of Boracay's rehabilitation strategies, and assessing the overall outcomes of the rehabilitation efforts. Employing a qualitative design through a case study method, information was gathered from twelve participants who were purposively chosen based on their direct involvement, expertise, experience, and roles in the Boracay rehabilitation. Through thematic analysis, key themes were identified that contributed to the understanding of environmentally-conscious tourism and rehabilitation strategies on the island. The findings reveal a positive behavioral change among participants toward environmental consciousness and practices due to their experiences with the Boracay rehabilitation. Strict regulatory measures and collaborative efforts among government entities, businesses, and residents have driven this behavioral shift. The study also found that effective rehabilitation strategies have led to environmental restoration, infrastructure improvement, and heightened community awareness and compliance with environmental regulations. Crucial strategies for achieving environmental success through the Boracay rehabilitation program include infrastructure investments, strict regulatory measures, and stakeholder collaboration. Despite initial economic hardships and concerns about governance, unfinished projects, and the sustainability of community compliance, the study concludes that the Boracay rehabilitation has successfully enhanced the island's environmental health, improved quality of life, and increased its attractiveness as a tourist destination. The study underscores the importance of continued collaboration among stakeholders to sustain the positive outcomes of the rehabilitation program, coupled with effective governance, adaptive policies, and strengthened education and awareness campaigns on Boracay Island.